Automated Quantification of Myocardial Salvage in a Rat Model of Ischemia–Reperfusion Injury Using 3D High‐Resolution Magnetic Resonance Imaging (MRI). Issue 4 (21st August 2014) - Grieve, Stuart M.; Mazhar, Jawad; Callaghan, Fraser; Kok, Cindy Y.; Tandy, Sarah; Bhindi, Ravinay; Figtree, Gemma A.
Abstract : Background: Quantification of myocardial "area at risk" (AAR) and myocardial infarction (MI) zone is critical for assessing novel therapies targeting myocardial ischemia–reperfusion (IR) injury. Current "gold‐standard" methods perfuse the heart with Evan's Blue and stain with triphenyl tetrazolium chloride (TTC), requiring manual slicing and analysis. We aimed to develop and validate a high‐resolution 3‐dimensional (3D) magnetic resonance imaging (MRI) method for quantifying MI and AAR. Methods and Results: Forty‐eight hours after IR was induced, rats were anesthetized and gadopentetate dimeglumine was administered intravenously. After 10 minutes, the coronary artery was re‐ligated and a solution containing iron oxide microparticles and Evan's Blue was infused (for comparison). Hearts were harvested and transversally sectioned for TTC staining. Ex vivo MR images of slices were acquired on a 9.4‐T magnet. T2* data allowed visualization of AAR, with microparticle‐associated signal loss in perfused regions. T1 data demonstrated gadolinium retention in infarcted zones. Close correlation ( r =0.92 to 0.94; P <0.05) of MRI and Evan's Blue/TTC measures for both AAR and MI was observed when the combined techniques were applied to the same heart slice. However, 3D MRI acquisition and analysis of whole heart reduced intra‐observer variability compared to assessment of isolated slices, and allowed automated segmentation and analysis, thus reducing interobserver variation. Anatomical resolution of 81 μm 3 was achieved (versus ≈2 mm with manual slicing). Conclusions: This novel, yet simple, MRI technique allows precise assessment of infarct and AAR zones. It removes the need for tissue slicing and provides opportunity for 3D digital analysis at high anatomical resolution in a streamlined manner accessible for all laboratories already performing IR experiments.